Changes in the Serum Protein Fractions in Goats after Treatment of Natural Gastrointestinal Parasite Infections - Frederika Chovanová; Csilla Tóthová; Róbert Klein; Oskar Nagy (Veterinary Medicine International)
Gastrointestinal parasitic infections in small ruminants belong to major health problems. The regulation of gastrointestinal infections in goats and the responses developed against them appear to be different from those observed in sheep. In the literature, there is a lack of data on the effect of gastrointestinal parasitic infections on the serum protein profile in goats. Therefore, the aim of the study was to determine the electrophoretic pattern of serum proteins in goats naturally infected with gastrointestinal parasites and to compare the changes in the total serum proteins and serum protein fractions (albumin and α1-, α2-, β-, and γ-globulins) obtained after antihelminthic treatment. Eight adult female goats of the white shorthaired breed from a small dairy goat farm at the age ranging between 3 and 5 years with average body weight 35.4 ± 3.2 kg and body condition score (BCS) from 1.5 to 2.5 were used in the study. The serum proteins in goats were separated into five fractions: albumin, α1- and α2-globulins, and β- and γ-globulins. Significant changes after treatment were found in the relative concentrations of albumin (P<0.01) and α2- (P<0.05), β- (P<0.001), and γ-globulins (P<0.01), as well as albumin/globulin ratio (P<0.01). The mean concentration of total serum proteins was, after the antiparasitic treatment, significantly higher. Among the globulin fractions, the γ-globulin fraction contributed most significantly to these changes (P<0.001). The results presented in the study suggest a significant effect of antiparasitic treatment in goats on the synthesis of blood serum proteins and on the changes of the proportion of serum protein fractions.